2016
DOI: 10.1016/j.ymgmr.2016.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Long-term galsulfase enzyme replacement therapy in Taiwanese mucopolysaccharidosis VI patients: A case series

Abstract: BackgroundInformation regarding the long-term outcome of enzyme replacement therapy (ERT) with recombinant human N-acetylgalactosamine 4-sulfatase (rhASB, galsulfase, Naglazyme®, BioMarin Pharmaceutical Inc.) for Taiwanese patients with mucopolysaccharidosis (MPS) VI is limited.MethodsNine Taiwanese patients with MPS VI (4 males and 5 females; age range, 1.4 to 21.1 years) treated with weekly intravenous infusions of galsulfase (1.0 mg/kg) in 5 medical centers in Taiwan were reviewed. A set of biochemical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 36 publications
(57 reference statements)
1
47
0
3
Order By: Relevance
“…Short stature in patients with MPS III is not as significant as that in other types of MPS, such as MPS IV, MPS VI, MPS I, and MPS II ( Lin et al, , Lin et al, ). For these 28 patients, the mean z scores for height and weight were −0.47 ± 1.97 and 0.02 ± 1.49, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Short stature in patients with MPS III is not as significant as that in other types of MPS, such as MPS IV, MPS VI, MPS I, and MPS II ( Lin et al, , Lin et al, ). For these 28 patients, the mean z scores for height and weight were −0.47 ± 1.97 and 0.02 ± 1.49, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that ERT for MPS I, II, IVA, and VI can lead to good clearance of urine GAGs and significantly improve a wide range of physiological activities and quality of life (Chuang et al, ; Harmatz, Giugliani, & Schwartz, ; Hendriksz et al, ; Lin et al, ; Lin, Chen, Chuang, et al, ; Lin, Chuang, Wang, et al, ; Muenzer et al, ; Ru et al, ; Wraith et al, ). The DMB ratio can provide useful information to evaluate the effectiveness of ERT from a biochemical point of view; however, it cannot directly reflect the efficacy of DS, HS, or KS degradation after ERT.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, 68 patients had available data on the presence of hernia, hepatosplenomegaly, claw hands, coarse face, adenotonsillar hypertrophy, valvular heart disease, joint stiffness, and hypermobile joints. Most of the patients (Chuang et al, 2017;Harmatz, Giugliani, & Schwartz, 2006, 2008Hendriksz et al, 2014Hendriksz et al, , 2016Lin et al, 2005;Lin, Chuang, Wang, et al, 2016;Muenzer et al, 2006;Ru et al, 2013;Wraith et al, 2004). The DMB ratio can provide useful information to evaluate the effectiveness of ERT from a biochemical point of view; however, it cannot directly reflect the efficacy of DS, HS, or KS degradation after ERT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapeutic options include bone marrow transplantation or enzyme replacement therapy (ERT) with supportive therapy. Long‐term galsulfase ERT was associated with improvements in physical endurance, pulmonary functions, stabilized cardiac function, increased survival, and decreased levels of urinary glycosaminoglycans (uGAGs) together with acceptable side effects were previously reported (Giugliani, Lampe, & Guffon, ; Harmatz et al, , , , , , ; Lin et al, ). Initiation of ERT at an earlier age facilitates better outcomes (Furujo, Kubo, Kosuga, & Okuyama, ; Harmatz et al, ; Horovitz et al, ; McGill et al, ).…”
Section: Introductionmentioning
confidence: 87%